Comparative Genomics RNAi Screen Identifies Eftud2 as a Novel Regulator of Innate Immunity - De Arras, Lesly (Genetics Society of America, 2014)
The extent of the innate immune response is regulated by many positively and negatively acting signaling proteins. This allows for proper activation of innate immunity to fight infection while ensuring that the response is limited to prevent unwanted complications. Thus mutations in innate immune regulators can lead to immune dysfunction or to inflammatory diseases such as arthritis or atherosclerosis. To identify novel innate immune regulators that could affect infectious or inflammatory disease, we have taken a comparative genomics RNAi screening approach in which we inhibit orthologous genes in the nematode Caenorhabditis elegans and murine macrophages, expecting that genes with evolutionarily conserved function also will regulate innate immunity in humans. Here we report the results of an RNAi screen of approximately half of the C. elegans genome, which led to the identification of many candidate genes that regulate innate immunity in C. elegans and mouse macrophages. One of these novel conserved regulators of innate immunity is the mRNA splicing regulator Eftud2, which we show controls the alternate splicing of the MyD88 innate immunity signaling adaptor to modulate the extent of the innate immune response.